Aspirin Triggered Resolvin D1 reduces inflammation and restores saliva secretion in a Sjögren's syndrome mouse model. (15th March 2019) - Dean, Spencer; Wang, Ching-Shuen; Nam, Kihoon; Maruyama, Christina L; Trump, Bryan G; Baker, Olga J
Abstract: Objectives: SS is characterized by chronic inflammation of the salivary glands leading to loss of secretory function, thereby suggesting specialized pro-resolving mediators targeting inflammation to be a viable option for treating SS. Previous studies demonstrated that aspirin-triggered resolvin D1 (AT-RvD1) prevents chronic inflammation and enhances saliva secretion in a SS-like mouse model when applied before disease onset. However, this therapy cannot be used in SS patients given that diagnosis occurs post-disease onset and no reliable screening methods exist. Therefore, we examined whether treatment with AT-RvD1 reduces SS-like features in a mouse model post-disease onset. Methods: Tail vein injections were performed in a SS-like mouse model both with and without AT-RvD1 post-disease onset for 8 weeks, with salivary gland function and inflammatory status subsequently determined. Results: Treatment of a SS-like mouse model with AT-RvD1 post-disease onset restores saliva secretion in both females and males. Moreover, although AT-RvD1 treatment does not reduce the overall submandibular gland lymphocytic infiltration, it does reduce the number of T helper 17 cells within the infiltrates in both sexes. Finally, AT-RvD1 reduces SS-associated pro-inflammatory cytokine gene and protein expression levels in submandibular glands from female but not male mice. Conclusion: AT-RvD1 treatment administered post-disease onset reduces T helper 17 cells and successfully restores salivary gland function in a SS mouse model with variable effects noted by sex, thus warranting further examination of both the causes for the sex differences and the mechanisms responsible for the observed treatment effect.